Effect of Workload on Nurse Work Stress at the Raja Ahmad Tabib Regional General Hospital, Riau Islands Province - Eka Kurnia Saputra; Satriadi Satriadi; Octojaya Abriyoso; Muhammad Rizki; Sella Titania (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine effect of workload on nurse work stress at the Raja Ahmad Tabib Regional General Hospital, Riau Islands Province. The method used in this study is an associative method with a quantitative approach. This study uses a saturated sampling method. The respondents of this study are 50 nurses at the Raja Ahmad Tabib Regional General Hospital, Riau Islands Province who specifically handled coronavirus disease 2019 (COVID-19). Collecting data using questionnaire techniques and literature study. The tool used is simple linear regression analysis, with partial test (t) and coefficient of determination test (R2). The results of this study indicate that workload has a positive and significant effect on nurse work stress with a significance value of 0.000<0.05. The workload at the Raja Ahmad Tabib Regional General Hospital, Riau Islands Province effect work stress by 65.9% while the remaining 34.1% is influenced by other variables.